In vitro antioxidant and antiproliferative activities of plants of the ethnopharmacopeia from northwest of Mexico - Jiménez-Estrada, Manuel (BioMed Central, 2013)
BACKGROUND: The aim of this study, is to investigate the in vitro antioxidant activity, the total phenols content, the flavonoids content and the antiproliferative activity of methanolic extracts of the plants: Krameria erecta, Struthanthus palmeri, Phoradendron californicum, Senna covesii and Stegnosperma halimifolium, used by different ethnic groups from northwestern Mexico in the treatment and cure of various diseases. METHODS: The in vitro antioxidant activity was measured by 2,2-diphenyl-1-picrylhydrazyl (DPPH) and Ferric Reducing/Antioxidant Power assay (FRAP), the total phenols content was measured by Folin–Ciocalteau assay, the flavonoids content by the AlCl(3) colorimetric method and the antiproliferative activity (line cells HeLa, RAW 264.7, M12A(k).C3.F6 and L929) using MTT method. RESULTS: The K. erecta extract showed the higher radical scavenging activity (67.88%), antioxidant activity by FRAP (1.41 mg Trolox Eq), the highest total phenols content (598.51 mg Galic Acid Eq/g extract), the highest flavonoids content (3.80 mg Quercetin Eq/g extract) and the greatest antiproliferative activity in a dose dependent manner against most Cell line evaluated. A positive correlation was found between the antioxidant activity and the flavonoids content. CONCLUSIONS: This study is the first report on the antioxidant and antiproliferative activities of the five species evaluated. The results demostrate that there is a positive correlation between antioxidant activity and the flavonoids content, indicating that these type of polyphenols could be the major contributors to the observed antioxidant activity in the evaluated plant extracts. Of the extracts evaluated, that of Krameria erecta showed the greatest antioxidant and antiproliferative activities, a discovery that makes this species a promising candidate for future research.